2015
DOI: 10.1007/s40429-015-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Environment Interplay and Substance Use: A Review of Recent Findings

Abstract: Substance use problems are chronic and common public health problems. We review recent studies that implicate genetic and environmental factors in their etiology. Although findings are mixed with respect to specific genotypes, some patterns are evident. For example, exposure to peers or parents who engage in high rates of substance use tends to exacerbate genetic diatheses or eliminate the protective effects of certain genotypes. We discuss reasons for mixed findings and highlight the need for translational re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…To the best of our knowledge, although G × E interactions are posited to play a central role in the pathogenesis of cannabis and tobacco use, very few studies have examined these mechanisms with most analyses focusing on serotonergic and dopaminergic genes. 138 From this perspective, our recent analyses underscore the importance of gender as a factor in these analyses. In addition to MAOA, only very few genes have been shown to interact with environmental factors to influence the risk for psychopathology in a sex-dimorphic fashion.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, although G × E interactions are posited to play a central role in the pathogenesis of cannabis and tobacco use, very few studies have examined these mechanisms with most analyses focusing on serotonergic and dopaminergic genes. 138 From this perspective, our recent analyses underscore the importance of gender as a factor in these analyses. In addition to MAOA, only very few genes have been shown to interact with environmental factors to influence the risk for psychopathology in a sex-dimorphic fashion.…”
Section: Discussionmentioning
confidence: 93%
“…These limitations notwithstanding, our data point to sex‐dimorphic G × E interactions in shaping the vulnerability for tobacco and cannabis use in college students. To the best of our knowledge, although G × E interactions are posited to play a central role in the pathogenesis of cannabis and tobacco use, very few studies have examined these mechanisms with most analyses focusing on serotonergic and dopaminergic genes . From this perspective, our recent analyses underscore the importance of gender as a factor in these analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in measurements among studies is a well-recognized problem in data aggregation. 17 The 3 non-replicated loci and the 6 loci without data for replication could represent falsepositive findings from GWAS, especially those for which there was no previous evidence supporting their potential involvement in the biological processes contributing to CUD. Nonetheless, among the 7 loci for which replication data were available, 4 were GWS either in replication or after combining results from the 2 analytic phases through meta-analysis, so they are worthy of further investigation.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, multiple studies have shown that the genetic risk for developing a substance use disorder can be moderated by environmental factors such as stressful life events, neighbourhood stability, religiosity and peer drug use. [12][13][14][15][16][17][18] Thus, the statistical power of genome-wide association studies (GWAS) to identify the genetic variation contributing to the risk of substance use disorders is limited by the extent to which environmental effects and phenotypic heterogeneity are unaccounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Protective effects of alcohol metabolism gene variants have been strongest in low-risk environments, remitting in high-risk peer or stressful family environments, 20,21 but see also Meyers and colleagues 22 . For example, carriers of another protective ADH1B variant, ADH1B*2 , were at lower risk for experiencing symptoms of alcohol use disorder than non-carriers, only when exposed to low levels of childhood adversity.…”
Section: Introductionmentioning
confidence: 99%